Exploring engineering an introduction to engineering and design - Kosky, P. G. (Philip G.) (Academic, 2012)
Suitable for those interested in exploring various fields of engineering and learning how engineers work to solve problems, this title explores the world of engineering by introducing the reader to what engineers do, the fundamental principles that form the basis of their work, and how they apply that knowledge within a structured design process.